THE CONTRIBUTION OF VACATION TO MALAYSIAN FAMILY WELLBEING: DESIGNING AND ANALYSING INSTRUMENT - Nurhazani Mohd Shariff; Noor Azimin Zainol; Noor Suhaila Yusof; Fauwaz Hasbullah; Chai Cheng Ho; Noor Sazali Mansor, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Nowadays, family vacation is becoming one of the most essential sectors of the tourism industry. It is a fact that family tourism and vacation provide benefits to family relationships, lifetime memories, communications, marriage, family happiness and also family wellbeing. A preliminary study involving 30 respondents was conducted to further design and analyse the instrument used to explore the contribution of vacation to the Malaysian family wellbeing. Several questions were proposed to fulfil the study; (1) Does vacation strengthen family bonding? (2) Does vacation contribute to the lifetime memories among family members? And (3) Does vacation create good communication among family members? The findings contributed to further study by using the tested instrument to fulfil the goal of the National Family Policy Malaysia (NFP) which aims to develop prosperous, healthy and resilient families to ensure social stability families. It significantly will support the Principle 4 of NFP which is to produce strong family relationships, a culture of sharing resources and mutual responsibilities to ensure family wellbeing. Further, the study is also significant to invigorating domestic tourism and ensuring business continuity by the Tourism, Arts and Culture Ministry.